Filter bank design for melody recognition - Gera, Zoltán (Acta Cybernetica, 2009)
Recognizing different features of a waveform to later recompose the music that was originally present in the signal is a difficult task. There are numerous fields of application where these techniques are known to be useful including music authoring, digitizer design, automatic music transcription. There are many different methods that can be used for this purpose giving somehow inadequate quality regarding noise, polyphony or time- / frequency localization compared to the human auditory system. In this article, I will show a new filter design method specifically designed to be aware of human perception features. I will also show the way how a complete filter bank can be assembled and used for melody recognition in real time. Finally, I will point out the benefits of this filter design compared to other methods.